Intersectional stigma and adherence to antiretroviral (ART) among sexual minority men (SMM) living with HIV in Nigeria: A Qualitative Inquiry - Adedotun Ogunbajo; Oluwatimilehin Sotubo; Kehinde Okanlawon; Elizabeth Shoyemi; Olakunle Oginni; Kenneth H. Mayer (PLoS ONE, 2025)
Background Sexual minority men (SMM) living with HIV in Nigeria experience suboptimal outcomes on the HIV care continuum. Experiences of intersectional stigma has been linked to lower likelihood of engagement in HIV services, but little is known about the effects of intersectional stigma on HIV care outcomes for SMM in Nigeria. The current study explored experiences of intersectional stigma among SMM living with HIV in Lagos, Nigeria and its’ impact on engagement in HIV care. Methods Between January and February 2022, we conducted semi-structured individual interviews with 30 SMM living with HIV in Lagos, Nigeria and 38 healthcare providers that provide HIV prevention and care services to SMM. Results We found that while participants described experiencing both HIV and sexual minority stigma, they believed sexual minority identity stigma to be more common than HIV-related stigma. Additionally, most participants believed they experience intersectional stigma, especially enacted and anticipated stigma, from their HIV status and sexual minority identity. Respondents utilized various strategies, both negative and positive, to cope with stigma including substance use, identity concealment, social isolation, support systems, and engaging in various hobbies as a form of self-care. Lastly, while most healthcare providers believe that stigma negatively influenced SMM ability to fully engage in HIV care, most SMM believed stigmatization had minimal to no effect on their engagement in HIV care. Discussion Our findings underscore the importance of developing community (SMM specifically) informed, evidence-based health interventions aimed at reducing the effect of stigma on engagement in HIV care among Nigerian SMM living with HIV, to improve their overall health and quality of life.